THE FLORAL COMPOSITION OF THE PLANT COMMUNITY ROSA POTENTILLIFLORA CHRSHAN. ET. M. POP. IN THE TURGEN GORGE OF THE TRANS - ILI ALATAU (Experimental biology, 2025)
The analysis of the flora of plant communities where a rare, endemic species Rosa potentilliflora Chrshan. et. M. Pop is found in the Turgen gorge of the Trans-Ili Alatau. Among the plants forming the community, Fabaceae Lindl. is in the first place, the genus consists of 10 species, or 12.6% of the flora. The main task of the park is to protect the magnificent, rich floral composition and vegetation of this mountain range, primarily rare, endangered endemic and relict species. The object of study can be in a natural way, with thunderstorms and just falling when there is a heavy downpour. Therefore, responsible employees of institutions such as the Trans-Ili Alatau National Park and Turgen Forestry should be aware that the Rosa potentilliflora plant is an endemic species requiring protection and is under constant supervision.
Keywords: flora, population, endemic, dominan, mesophyte, xerophyte, hemicryptophyte, terophyte